Extending taxation of interest and royalty income at source: An option to limit base erosion and profit shifting? - Katharina Finke; Clemens Fuest; Hannah Nusser; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper discusses tax policy measures to reduce corporate tax avoidance by extending taxation in the source country without imposing double taxation. We focus on four options: Bilaterally restricting interest and royalty deductibility, introducing an inverted tax credit system, levying withholding taxes on all interest and royalty payments and levying withholding taxes as an anti-avoidance regulation. We calculate the tax revenue effects of introducing a minimum withholding tax on royalty payments and an inverted tax credit. For the withholding tax we find that the US would suffer the greatest tax revenue losses, while some other countries would increase their tax revenue. In general, gains and losses depend not only on net balances in royalty income flows but also on withholding tax and credit rules under the status quo. The inverted tax credit would increase tax revenue in particular in high-tax countries. Revenue redistribution would only arise if withholding taxes were replaced by the inverted credit.
urn:nbn:de:bsz:180-madoc-371828
Keywords: H20; H21; H32; F23; K34; 330; profit shifting; multinational firm; source taxation; tax policy; tax reform; optimal taxation